Effectiveness of Gagné’s 9 Events of Instruction in health professions education: a systematic review and meta-analysis - Li, Yue; Liang, Zhengjv; Li, Zhongyan; Yu, Yuhuan; Yang, Qing; Li, Xiao (Frontiers in Medicine, 2025)
ObjectiveThis review assesses the effectiveness of Gagné’s 9 Events of Instruction in improving theoretical scores and clinical practice abilities in medical education.MethodsThis study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two researchers conducted a comprehensive search of Chinese and English electronic databases (Web of Science, PubMed, Embase, Cochrane Library, CNKI, VIP, Wanfang). The participants included clinical medical students, nursing students, specialized medical students, and medical interns, among others related to healthcare. Educators used Gagné’s 9 Events of Instruction to guide these populations in theoretical learning and/or daily clinical practice. The search was conducted from the inception of the databases to February 27, 2025. Two researchers independently identified, selected, and extracted data from the studies, assessed the quality using the Cochrane Risk of Bias tool, and performed meta-analyses using RevMan 5.4 and Stata 17.0.ResultsA total of 11 studies involving 825 participants were included in the meta-analysis, including 5 RCTs and 6 CSs. In the cumulative meta-analysis, compared with the traditional LBL model, Gagné’s 9 Events of Instruction significantly improved learners’ KES (SMD 1.55, 95% CI: 0.81 to 2.29; p < 0.00001), PS (SMD 1.83, 95% CI: 1.19 to 2.47; p < 0.00001), LC (OR 4.92, 95% CI: 3.13 to 7.73; p < 0.0001), and TS (OR 7.86, 95% CI: 3.22 to 19.20; p < 0.0001).ConclusionThe meta-analysis indicated that, compared to traditional medical teaching models, Gagné’s 9 Events of Instruction are significantly effective in health professions education and can effectively enhance learners’ KES, PS, LC, and TS.